Comparison of phenylephrine and norepinephrine for prevention of hypotension in patients undergoing cesarean section under spinal anesthesia - A randomized prospective study - Wakhloo Renu; Bhagat Heena; Gandotra Megha; Suri Era (Wolters Kluwer Medknow Publications, 2022)
Background: Hypotension is a common side effect of spinal anesthesia for cesarean section with incidence of upto 71%. Various vasopressors are available for counteracting spinal hypotension each with different pharmacological profile. Norepinephrine is currently one of the feasible options for prophylaxis of spinal induced hypotension in patients undergoing cesarean section. Aims: To compare efficacy of phenylephrine and norepinephrine for reducing incidence of hypotension in patients undergoing cesarean section under spinal anesthesia and their effect on neonatal outcome. The primary outcome compared was incidence of hypotension (defined as fall in systolic blood pressure of >20% from the baseline value or a value <90 mmHg). The secondary outcomes noted were incidence of bradycardia, nausea, vomiting in the mother, and neonatal outcome. Methodology: A total of 80 singleton full term pregnant patients of American Society of Anesthesiology (ASA) grade II scheduled for elective cesarean section were randomly assigned to 2 groups of 40 patients each. Group P received phenylephrine 50 mcg and Group N received norepinephrine 10 mcg as intravenous bolus over 1 min immediately after the patient had been made supine after giving spinal anesthesia. The vital parameters, adverse effects, and neonatal outcome were assessed and analyzed statistically. Results: Intraoperatively, norepinephrine group had a significantly higher mean heart rate than phenylephrine group. Neonatal outcome was similar in both the groups with respect to appearance, pulse, grimace, activity, and respiration (Apgar) scores and umbilical arterial pH. Conclusions: In cesarean section under spinal anesthesia, norepinephrine efficacy in rescuing maternal hypotension is similar to that of phenylephrine without obvious maternal or neonatal adverse outcomes and with a lower incidence of bradycardia.